The 10th anniversary of the gymnasium las palmas (Fiep Bulletin - online, 2015)
The Canary Islands constitute two Spanish provinces formed of 7 islands and some islets in the Atlantic Ocean facing the African Coast of the Sahara. Enjoying a spring-like climate the whole year, the geographical situations makes of certain regions of the archipelago a thoroughfare for the navigation between Europe, Africa, America and the Middle East and a refuge for numerous tourists who flee from the cold and mists of the northen regions.